Sanghyang Sampat Dance in Puluk - Puluk Village as an Idea for Creating Painting Works - Putra, I Gede Agus Adnyana; Supriyatini, Sri; Tjokropramono, I Gede Yosef (Program Studi Seni Murni ISI Bali, 2023)
This independent study report has the theme Sanghyang Sampat Dance in Puluk-Puluk Village as an Idea to Create Paintings. The choice of partners in Galung Wiratmaja is due to their different characteristics from the others. The specialty in terms of choosing color mixing, the choice of painting objects tends to be in the form of imagination in the form of the natural environment. The visual appearance created has an appeal, because taking objects displays the back of the object and creates an impression of interest to those who see it. Sanghyang Sampat is a tradition that developed in the village of Puluk-Puluk Penebel, Tabanan, this tradition exists for the welfare of people who have livelihoods as farmers. Sanghyang Sampat dance is a Bugis tradition that is highly trusted by the local community. Art as an element of culture is also born as a result of the demands of religious activity. There are many ways to preserve the Sanghyang Sampat Dance Tradition, one of which is by visualizing the dance in a painting medium, to encourage the creation of various symbolic-magical art forms which are representations of something abstract. In inspiring the Sanghyang Sampat Dance, artists process their visual forms into forms of personal expression, and there are also those who bring it up through an interpretation of the meaning and value of sanghyang sampat, which in visualization may give rise to new forms as personal codes. in his work. In this case, the Sanghyang Sampat Dance is a source of ideas for artists in creating modern works of art without leaving traditional values behind.